Cross-sectional analysis of delays in care and interactions with healthcare providers among transgender and gender diverse individuals - Hill, Kasey A.; Carrasquillo, Olveen; Medina Laabes, Diana T.; Colón-López, Vivian (Frontiers in Health Services, 2025)
IntroductionTimely access to positive, culturally competent healthcare experiences may be critical for transgender and gender diverse (TGD) individuals. However, gaps remain in our understanding of TGD individuals’ access to these experiences. Our aim was to determine whether TGD individuals’ likelihood of reporting delays in care and positive healthcare provider interactions differs from that of cisgender people.MethodsWe analyzed survey data from 89,133 participants who enrolled in the National Institutes of Health's All of Us Research Program from 5/6/2018 to 4/1/2021. Unadjusted and adjusted logistic regressions were performed to assess the association of gender with delays in care in the past 12 months and provider interactions.ResultsAfter adjustment, TGD individuals were more likely than cisgender men to report eight of nine reasons for care delays and more likely than cisgender women to report two of nine reasons. TGD individuals were more likely than cisgender men (OR: 2.20, 95% CI: 1.88–2.58, p < .001) or women (OR: 1.45, 95% CI: 1.24–1.70) to report delaying care for any reason enquired about on the survey. TGD individuals were less likely than cisgender men to report all three types of positive healthcare provider interactions and were less likely than cisgender women to report two of three types of positive interactions.ConclusionOur findings indicate that TGD individuals may be more likely than cisgender people to experience delays in care and less likely to experience positive healthcare provider interactions. This suggests a critical need to increase TGD individuals’ access to supportive, culturally competent healthcare providers.